A very rare variant in the colon supply--arteria mesenterica media - Kachlik, David; Laco, Josef; Turyna, Radovan; Baca, Vaclav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2009)
AIMS: The arteria mesenterica media is a very rare variation of the mesenteric blood supply. It is a direct branch from the aorta abdominalis originating between the arteria mesenterica superior and inferior. This is not an aim. METHODS: One hundred forty-nine large intestines from cadavers fixed with formaldehyde were dissected. RESULTS: A case of the present arteria mesenterica media was discovered during the dissection of the large intestine blood supply. It originated from the anterior wall of the aorta abdominalis 2 cm above the arteria mesenterica inferior origin, having the diameter 0.9 mm. Then it ran horizontally to the left giving off branches to the colon descendens and flexura coli sinistra, in the extent of the normal arteria colica sinistra. DISCUSSION: Seventeen cases of true arteria mesenterica media have been reported since 1952. CONCLUSION: The term arteria mesenterica media must be reserved for the vessel stemming from the aorta abdominalis in the extent between the arteria mesenterica superior and inferior.
Keywords: Colon; arteriae mesentericae; Mesenteric Arteries; Humans; kolon; lidé